The Study of Social Interaction in Education and Its Influence on Sociology Learning Achievement in Students - Ibrahim Nurdin; Jumadi Jumadi; Syamsu Kamaruddin (Universitas Negeri Makassar, 2023)
The purpose of this study was to determine the significant effect of social interaction in education on student achievement in sociology at SMA Negeri 1 Pangkep. The method used in this research is experimental research with correlation studies. The results showed that tcountof 2.20 indicates that there is an effect of the independent variable (X) on the dependent variable (Y). When compared to ttable is 2.00 then tcount greater than ttableor 2.20>2.00 so that Ha is accepted and Ho is rejected. This means that there is a significant influence between social interaction in education on the sociology learning achievement of students in SMA Negeri 1 Pangkep